1D and 2D NMR spectroscopy for identification of carbamide-containing biologically active compounds - Bakibaev, A.A.; Panshina, S.Yu.; Ponomarenko, O.V.; Malkov, V.S.; Kotelnikov, O.A.; Tashenov, A.K. (KU Publ., 2021)
Urea (carbamide) is the main end product of amino acids' metabolism in mammals. Extensive research in the field of urea chemistry has contributed to the creation of many biologically active and other compounds based on the carbamide fragment NH–CO–NH. The substituting groups of urea directly affect its properties and characteristics which are reflected in the NMR spectral data and this circumstance can be the basis for the identification of urea derivatives. In this work, chemical shifts in the NMR spectra of urea and its acyclic structure, barbituric series, imidazolidinone series and bicyclic structure derivatives were studied and identified. A system analysis was carried out to determine the effect of the type of substituents on the positions of signals of the NH-CO-NH fragment in the NMR spectra. The possibility of 2D NMR spectroscopy using to simplify the identification procedure for complex mixtures was shown in the paper. The combined use of 1D and 2D NMR spectroscopy is convenient and informative to establish the structure of biologically active compounds. These methods make it possible to determine the presence and type of impurities, as well as to establish the destruction processes leading to the corresponding impurities.
Мочевина құрамындағы биологиялық белсенді қосылыстарды анықтауға арналған 1D және 2D NMR спектроскопиясы
1D и 2D ЯМР-спектроскопия для идентификации карбамидсодержащих биологически активных соединений
Keywords: urea; urea-containing compounds; barbiturates; glycoluril; imidazolidinone; NMR spectroscopy; hydrolysates; impurities